Peaceful Coexistence between Muslims and Christians in Light of the Purposes of Sharia : (Koya city as a model) - Ribwar Hameed Abdullah; Jawad Faqi Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
It is one of Allah's rules that there are different races and diverse religions, sects, and backgrounds in His creation. The Holy Qur’an approved coexistence, and the Sunnah confirmed it on more than one occasion. In this way, Islam dealt with others and established rules for peaceful coexistence. The goal was to achieve justice among all without discrimination or preference based on human unity, freedom of belief, and equality. The purpose of this research is to explore the concept of peaceful coexistence in Islam, its principles, and foundations from the Shariah perspective. One of the most important objectives of the Shariah is to preserve the necessities of religion, soul, mind, offspring, and money, and to achieve a secured life in peaceful coexistence condition by keeping its pillars side by side justice and freedom despite a variety of beliefs, colours, languages, and races. Taking into consideration the spirit of tolerance and coexistence between Muslims and Christians in the city of Koya, the research examines how to flourish and develop this peaceful coexistence. It then explores the issues that could hinder coexistence between Muslims and Christians so long as the goal of coexistence demands a return to Koya's past days and learning from it for the present. Hence, this research is divided into an introduction, three chapters, and a conclusion. Chapter One is dedicated to the general literature on peaceful coexistence and its foundations, while Chapter Two discusses the purposes and their relationship to peaceful coexistence. Chapter Three examines peaceful coexistence between Muslims and Christians in the city of Koya, which will be followed by the conclusion highlighting its most pertinent findings and recommendations.